Chronic thromboembolic pulmonary hypertension secondary to a vascular malformation: case report diagnosis by lung subtraction iodine mapping - Fawzy, Aly; Mafeld, Sebastian; Oreopoulos, George; de Perrot, Marc; McInnis, Micheal C. (Frontiers in Medicine, 2023)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a challenging diagnosis that can occur even in the absence of a prior thrombotic event. The main screening test is ventilation-perfusion (VQ) scintigraphy. The gold standard treatment for CTEPH is pulmonary endarterectomy (PEA), however, balloon pulmonary angioplasty (BPA) is an emerging treatment, especially for CTEPH at the segmental level. We report on a case of a patient with segmental CTEPH diagnosed by lung subtraction iodine mapping (LSIM) in the context of a chest wall vascular malformation. CTEPH was treated with BPA and by embolization and ligation of their vascular malformation.